Pemberian Kompos dan Eco Farming terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) - Eva Trisnayani; Dermawan Hutagaol; Aisyah Lubis (Jurnal Agrofolium, 2023)
The purpose of this study is to analyze the effects of decomposition, eco-farming, and their interactions on the development and harvest of shallots (Allium ascalonicum L.).This research used a two-factor, three-cycle randomized factorial block design. Compost (K) application came first, and that was done on three different stages.: K0 = no treatment (control), K1, K2, and K3., K1 = 1.5 kg plot-1 and K2 = 3 kg plot-1. The second factor of Eco Farming (E) consists of 4 levels, namely E0 = no treatment (control), E1 = 1.5 ml L-1 of water, E2 = 3 ml L-1 of water and E3 = 4.5 ml L-1 of water. Parameters observed were plant height , number of tillers per clump and tuber weight per plot .The results showed that compost application significantly impacted plant height and tuber weight per plot, but not tillers per cluster. Eco-farming's inclusion has a highly significant effect on plant height, a noticeable effect on tuber weight per acre, but no discernible effect on tillers per cluster. None of the measured variables were affected significantly by the composting and sustainable agriculture interaction treatment.